2021
DOI: 10.3389/fnbeh.2021.690344
|View full text |Cite
|
Sign up to set email alerts
|

HINT1 Is Involved in the Chronic Mild Stress Elicited Oxidative Stress and Apoptosis Through the PKC ε/ALDH-2/4HNE Pathway in Prefrontal Cortex of Rats

Abstract: Major depressive disorder (MDD) is a severe, highly heterogeneous, and life-threatening psychiatric disease which affects up to 21% of the population worldwide. A new hypothesis suggests that the mitochondrial dysfunction causing oxidative stress (OS) and dysregulation of apoptosis in brain might be one of the key pathophysiological factors in MDD. Histidine triad nucleotide binding protein 1 (HINT1), which was first supposed to be protein kinase C (PKC) inhibitor, has been gradually demonstrated to be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…SIRTs are NAD-dependent deacetylases and ALDHs are responsible for the removal of toxic intermediate aldehyde products. It has been shown that both genetic markers play essential roles in the NAD-related pathways and may be associated with the pathology of MDD [27,30]. Therefore, all SIRTs and ALDHs genes were also included in our search.…”
Section: Methodsmentioning
confidence: 99%
“…SIRTs are NAD-dependent deacetylases and ALDHs are responsible for the removal of toxic intermediate aldehyde products. It has been shown that both genetic markers play essential roles in the NAD-related pathways and may be associated with the pathology of MDD [27,30]. Therefore, all SIRTs and ALDHs genes were also included in our search.…”
Section: Methodsmentioning
confidence: 99%
“…The SPT is used to test for anhedonia which is one of the core symptoms of depression and a sign of the success of the CUMS model [ 25 ]. This experiment was divided into training and testing stages.…”
Section: Methodsmentioning
confidence: 99%
“…As Hint1 has been shown to participate in the regulation of the apoptotic pathway [12], it is likely to be involved in the process of angiogenesis and skeletal muscle regeneration in areas of hindlimb ischemia with ischemic necrosis, where monocytes and macrophages are known to play a critical role [23]. To investigate whether Hint1 deficiency affects the inflammatory condition of ischemic muscle, we performed flow cytometry to measure muscular inflammation.…”
Section: Hint1 Deficiency Barely Affects Inflammation In Ischemic Mus...mentioning
confidence: 99%
“…Hint1 is involved in mitochondrial-related oxidative stress and apoptosis [23]. Hint2, an isomer of Hint1, is an important mitochondrial enzyme with similar substrate specificities with Hint1 [24].…”
Section: The Silencing Of Hint1 Damages Mitochondrial Function In Ecsmentioning
confidence: 99%